ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KEBIJAKAN DIVIDEN - Welas Welas; Sudiyatno Yudi Nugroho (LPMP Imperium, 2019)
The purpose of this research is to study the influence of cash position, Total Assets Turnover (TATO), Return On Assets (ROA) and Debt to Total Assets (DTA) on the Dividend Payout Ratio (DPR). The sample used in this study is the company incorporated in the Business Index 27 on the Indonesia Stock Exchange for the period 2013-2017. The technique used in sampling is purposive sampling with secondary data in the form of financial statements. The data analysis tool in this study uses multiple linear regression. Data testing consists of classic assumption and hypothesis testing. The results of this study indicate that the variables TATO and DTA affect the DPR while the variable cash position and ROA have no effect on the DPR. Discussion and implication were suggested in the paper.